2007
DOI: 10.1038/cr.2007.110
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced cell death: lessons from the central nervous system

Abstract: npg DNA damage can, but does not always, induce cell death. While several pathways linking DNA damage signals to mitochondria-dependent and -independent death machineries have been elucidated, the connectivity of these pathways is subject to regulation by multiple other factors that are not well understood. We have proposed two conceptual models to explain the delayed and variable cell death response to DNA damage: integrative surveillance versus autonomous pathways. In this review, we discuss how these two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 78 publications
2
95
0
1
Order By: Relevance
“…We found that cell death depended on incubation time after UV irradiation, and cell death after irradiation was not significantly reduced until 24 h at all wavelengths. Cell death occurs from irreparable DNA damage that remains 24-48 h after UV exposure [19,40].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…We found that cell death depended on incubation time after UV irradiation, and cell death after irradiation was not significantly reduced until 24 h at all wavelengths. Cell death occurs from irreparable DNA damage that remains 24-48 h after UV exposure [19,40].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…In animals, cell death downstream of ATM or ATR activation is usually mediated by p53 and occurs through apoptosis (13,30). Plants do not have recognizable homologs of p53 or core regulators and executioners of apoptosis, such as APAF1, BCL2, or caspases (19).…”
Section: Programmed Death After Dna Damage Showed Autolytic Rather Thanmentioning
confidence: 99%
“…Conformational changes of DNA, manifested as double-strand breaks, mispairings, or modifications in the nucleosides, can be related to diseases, ageing or cell death [1][2][3][4] . One way to detect these conformational changes is by employing electron paramagnetic resonance (EPR) techniques which can provide structural information [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%